FROM EXPERIENCE OF TEACHING BIOCHEMISTRY IN THE HIGHER SCHOOL - Svetlana Andrusenko; Evgenija Denisova; Anastasia Filippova (Вестник Северо-Кавказского федерального университета)
In article questions of improvement of quality of knowledge and improvement of vocational training of students at the North Caucasian federal university on an example studying of discipline "Biochemistry" are considered. Mnemotekhnichesky methods of storing of terms and difficult multichained reactions are described. Experience of holding the Olympic Games on biochemistry developing cognitive interest and creative abilities of students is given. One of ways of fixing and control of the gained knowledge in the form of different types of testing is reflected. Experience of introduction of courses of additional education is given as the new area of work with students beyond the scope of the usual program. Author's technologies in the development of the electronic textbook and an electronic laboratory video workshop on biochemistry expanding possibilities of use of a visual and demonstration training material with involvement in process of training of acoustical and emotional memory are presented.